Early versus delayed stenting for intracranial atherosclerotic artery stenosis with ischemic stroke. (8th July 2019) - Zhang, Yong; Sun, Yujie; Li, Xin; Liu, Tonghui; Liu, Peng; Wang, Hongxia; Ding, Jian; Miao, Zhong-Rong; Li, Guangwen
Abstract : Objective: To evaluate the clinical outcomes of early stenting (≤14 days) or late stenting (>14 days) in patients who underwent intracranial stent placement. Methods: Patients with ischemic stroke caused by 70–99% intracranial atherosclerotic stenosis combined with poor collaterals were enrolled. The early stenting group, who underwent stenting within 14 days of last ischemic symptoms, were compared with the late stenting group who underwent stenting >14 days from last ischemic symptom. The patients were treated either with a balloon-mounted stent or a self-expanding stent as determined by the operators following a guideline. The baseline characteristics and clinical outcomes were evaluated and compared. Results: One hundred and fifteen stroke patients were recruited into the study. Four patients (4/41) in the early stenting group and two patients (2/74) in the late stenting group were diagnosed with a cerebral vascular event associated with stenting within 3 days (p=0.184). In the long-term follow-up, eight patients in the early stenting group had restenosis ≥50%, which was higher than patients in the late stenting group (8/41 vs 4/74, p=0.018). The total rates of any ischemic stroke, transient ischemic attack, hemorrhagic stroke, and death in the early stenting group were higher than in the late stenting group (9/41 vs 6/74, p=0.035). The recurrence rate of ischemic stroke in the early stenting group was higher than in the late stenting group (5/41 vs 2/74, p=0.041). Conclusions: Stent placement in the setting of ischemic stroke caused by intracranial artery stenosis within 14 days may confer a higher risk of long-time cerebral vascular events and lead to a higher risk of restenosis. Clinical trial registration: NCT01968122 .